(untitled) (World of finance, 2021)
Introduction. The dynamic extensive development of the world economy during the twentieth and twenty-first centuries has led to a significant deterioration of the ecological situation of industrial regions and raised the question of finding the optimal balance between output growth and environmental protection. One of the important regulatory mechanisms available to the state is environmental taxation. The purpose of this tax is to contain and compensate for environmental damage caused by human activities through the introduction of mandatory payments. However, the object and base of taxation, the name of taxes and further use of funds raised by them are different and depend on the country. The main environmental payment is the ecological tax in Ukraine. Decentralization, one of the key reforms in the country, aims to transfer resources and responsibilities from the central to the local level. Thus, it is important to find an appropriate and reasonable distribution of revenues from the environmental tax between the budgets of state, regional and local levels. The purpose of the article is to research the organizational and legal bases of modern foreign and domestic complexes of nature protection payments in the context of reform of local self-government and territorial organization of power. Results. The current world and national experience in the field of taxation in order to protect the environment is analyzed. The current state of affairs of the environmental tax in Ukraine is revealed. Further directions of research on this topic are outlined.